2012
DOI: 10.2164/jandrol.111.014944
|View full text |Cite
|
Sign up to set email alerts
|

Soy Lecithin Interferes With Mitochondrial Function in Frozen‐Thawed Ram Spermatozoa

Abstract: Egg yolk and milk are the 2 major membrane cryoprotectants commonly used in freezing media for the long-term preservation of semen (alone or in combination with others). However, in recent years, there have been increasing arguments against the use of egg yolk or milk because of the risk of introducing diseases through the use of cryopreserved semen. In this study, we analyzed the protective effect of lecithin as an alternative to egg yolk for the cryopreservation of ram semen, using a range of functional mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
36
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 56 publications
8
36
0
1
Order By: Relevance
“…Tales condiciones pueden explicar la presencia de diferentes patrones de motilidad (cinemática) que caracterizan a las subpoblaciones espermáticas, y cambios en la proporción de estas poblaciones pueden afectar el éxito en el proceso de fertilización como se ha descrito en ovinos (4), en venado rojo ibérico (31), humano (32), entre otras especies. Desde hace dos décadas el estudio de las subpoblaciones ha tenido relación con la fertilidad (33 …”
Section: Discussionunclassified
“…Tales condiciones pueden explicar la presencia de diferentes patrones de motilidad (cinemática) que caracterizan a las subpoblaciones espermáticas, y cambios en la proporción de estas poblaciones pueden afectar el éxito en el proceso de fertilización como se ha descrito en ovinos (4), en venado rojo ibérico (31), humano (32), entre otras especies. Desde hace dos décadas el estudio de las subpoblaciones ha tenido relación con la fertilidad (33 …”
Section: Discussionunclassified
“…Supporting this theory, Masoudi's et al (2016) showed that 1% soybean lecithin extenders have similar effects on post-thawed sperm quality with 20% egg yolk extenders. Notwithstanding the abovementioned positive properties of soybean lecithin, other surveys have noticed some detrimental effects of higher soy lecithin concentrations on post thaw ram semen quality (Mata-Campuzano et al, 2015;Valle et al, 2012). Although it is effective in protection of basic sperm quality characteristics against freezing-induced damage, high concentration of it (3.5%) induces loss of mitochondrial membrane potential without any significant reflection in motility (Valle et al, 2012).…”
Section: Results Publicationmentioning
confidence: 99%
“…Notwithstanding the abovementioned positive properties of soybean lecithin, other surveys have noticed some detrimental effects of higher soy lecithin concentrations on post thaw ram semen quality (Mata-Campuzano et al, 2015;Valle et al, 2012). Although it is effective in protection of basic sperm quality characteristics against freezing-induced damage, high concentration of it (3.5%) induces loss of mitochondrial membrane potential without any significant reflection in motility (Valle et al, 2012). Mitochondrial membrane potential is a parameter that has been considered as a good indicator of sperm functionality which affects fertilizing capacity.…”
Section: Results Publicationmentioning
confidence: 99%
“…A recent study by Del Valle et al [2012] indicates that SPC interferes with mitochondrial function of ram spermatozoa. In the present study even though we have not assessed mitochondrial function, the longevity in survival of spermatozoa cryopreserved in liposome based medium indicates that the substitution of egg yolk with SPC and cholesterol in liposome encapsulated form may not have any adverse effects on sperm mitochondrial function.…”
Section: Discussionmentioning
confidence: 98%